Secure Coding: Principles & Practices - Graff, Mark G. (O'Reilly, 2011)
Despite their myriad manifestations and different targets, nearly all attacks on computer systems have one fundamental cause: the code used to run far too many systems today is not secure. Flaws in its design, implementation, testing, and operations allow attackers all-too-easy access. Secure Coding: Principles & Practices looks at the problem of bad code in a new way. Packed with advice based on the authors' decades of experience in the computer security field, this concise and highly readable book explains why so much code today is filled with vulnerabilities, and tells readers what they must do to avoid writing code that can be exploited by attackers.